2010
DOI: 10.1159/000276595
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islet Transplantation Using Vascularised Chambers Containing Nerve Growth Factor Ameliorates Hyperglycaemia in Diabetic Mice

Abstract: Intraportal islet transplantation has shown initial promise for the treatment of type 1 diabetes. However, the portal vein site is associated with complications such as thrombosis and hepatic steatosis, leading to transplant failure. The aims of this study were to (1) test the feasibility of an alternative islet transplantation method that utilises a FDA-approved gelatin sponge as a novel islet carrier and (2) assess if exogenous addition of nerve growth factor (NGF) has any additional beneficial effects on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 64 publications
3
16
0
Order By: Relevance
“…Any NGF effect on inter-islet neurovascular enrichment would be more evident when islets are clustered together under the kidney capsule 20 or in biocompatible synthesized chambers. 23 This juxtaposition of islets may also explain the higher efficiency of subcapsular transplants.…”
Section: Do Not Distributementioning
confidence: 99%
See 1 more Smart Citation
“…Any NGF effect on inter-islet neurovascular enrichment would be more evident when islets are clustered together under the kidney capsule 20 or in biocompatible synthesized chambers. 23 This juxtaposition of islets may also explain the higher efficiency of subcapsular transplants.…”
Section: Do Not Distributementioning
confidence: 99%
“…20 Moreover, islets were efficiently transplanted in vascularized chambers based on the neurovascular support from the femoral artery, vein and nerve, in the presence of a gelatin sponge scaffold with NGF. 23 However, the usefulness of NGF in intraportal islet transplantation was still unknown. To resolve this problem, we transplanted syngeneic islets (360 islet equivalents per recipient) cultured with or without 2.5S mouse NGF for 24 h into the portal vein of streptozotocin-induced diabetic BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NGF treatment also increases insulin secretion in cultured islet (Rosenbaum et al 2001), as well as in transplanted islet (Miao et al 2005). Injection of 6 μg NGF can restore the glucose tolerance in male Balb/c mice to the level that is comparable to that of islet transplanted mice (Miao et al 2005), or the non-diabetic control mice (Hussey et al 2010). …”
Section: Nerve Growth Factormentioning
confidence: 94%
“…However, exogenous insulin was still required [82]. A modified approach was taken by Cronin et al [83] in a diabetic mouse model, which involved running a portion of the femoral artery though the lumen of a silicone tube, which was filled with a Matrigel® (BD Biosciences, Franklin Lakes, NJ) solution supplemented with FGF and heparin [84] or Gelita-Spon® (Gelita Medical BV, Amsterdam, Netherlands) supplemented with nerve growth factor (NGF) [85]. In the matrigel study, islets were seeded at the time of implantation or 3 weeks after prevascularization of the chamber.…”
Section: Improving An Islet’s Homementioning
confidence: 99%
“…Interestingly, the later study demonstrated that prevascularization of the chamber was not required when syngeneic islets were seeded with NGF. In this condition, 80% of mice achieved normoglycemia compared with 0% of mice receiving islets on the gelatin sponge alone [85]. This system takes advantage of an easily vascularized transplantation site, which allows optimal diffusion while eliminating protein deposition and coagulation around the graft.…”
Section: Improving An Islet’s Homementioning
confidence: 99%